Extracellular vesicles in human follicular fluid do not promote coagulation - Franz, Cordula; Böing, Anita N.; Montag, Markus; Strowitzki, Thomas; Markert, Udo R.; Mastenbroek, Sebastiaan; Nieuwland, Rienk; Toth, Bettina (Reproductive biomedicine online, 2016)
Body fluids contain extracellular vesicles expressing tissue factor on their surface and serve as an additional trigger for coagulation. During the menstrual cycle ovarian tissue restoration is mandatory and it is unknown whether follicular fluid might provide procoagulant substances. Within an observational study, follicular fluid from women undergoing IVF/intracytoplasmic sperm injection (ICSI) was analysed by fluorescence-activated cell sorting (FACS), electron microscopy, resistive pulse sensing (RPS), nanoparticle-tracking analysis (NTA) and fibrin generation tests (FGT). The presence of extracellular vesicles, especially CD9-positive extracellular vesicles in follicular fluid, was proven. However, clotting tests revealed no procoagulant properties of the detected extracellular vesicles.
Gesehen am 25.05.2020